A Study of Mild Steel Corrosion Using Adhatoda Vasica (AV) Extract as Inhibitor in Different Acid Medium. Issue 4 (2010) - Matheswaran, P.; Ramasamy, A. K.
Abstract : Corrosion behavior of mild steel in acidic medium using Adhatoda Vasica (AV) extract was investigated. The inhibitive effective of Adhatoda Vasica on the corrosion of mild steel in different acidic medium has been studied by weight loss and polarization methods. The Ecorr values are shifted slightly towards negative side in presence of inhibitors which indicate the inhibitors inhibit the corrosion of mild steel in acids solution by controlling both anodic and cathodic reactions due to the blocking of active sites on the metal surface. It is evident that inhibitors bring about considerable polarization of the cathode as well as anode. It was, therefore, inferred that the inhibitive action is of mixed type.